2020
DOI: 10.1021/acsami.0c06926
|View full text |Cite
|
Sign up to set email alerts
|

PEG/PPG–PDMS-Based Cross-Linked Copolymer Membranes Prepared by ROMP and In Situ Membrane Casting for CO2 Separation: An Approach to Endow Rubbery Materials with Properties of Rigid Polymers

Abstract: Rubbery polymer membranes prepared from CO2-philic PEO and/or highly permeable PDMS are desired for efficient CO2 separation from light gases (CH4 and N2). Poor mechanical properties and size-sieving ability, however, limit their application in gas separation applications. Cross-linked rubbery polymer-based gas separation membranes with a low T g based on both PEG/PPG and PDMS units with various compositions between these two units are prepared for the first time in this work by ring-opening metathesis polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 67 publications
8
75
1
Order By: Relevance
“…Furthermore, in the x(10:0.5:0.5) membrane, despite decreasing PDMS content, the degree of permeability was found to increase, and a loss of permeability was observed in the x(10:0:1) membrane. This trend differs from that in our previous reports of permeability and selectivity for crosslinked membranes made of only PEG/PPG and PDMS [ 23 ], where the permeability increased while the selectivity decreased with an increase in PDMS content.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, in the x(10:0.5:0.5) membrane, despite decreasing PDMS content, the degree of permeability was found to increase, and a loss of permeability was observed in the x(10:0:1) membrane. This trend differs from that in our previous reports of permeability and selectivity for crosslinked membranes made of only PEG/PPG and PDMS [ 23 ], where the permeability increased while the selectivity decreased with an increase in PDMS content.…”
Section: Resultscontrasting
confidence: 99%
“…Nevertheless, the diffusivity of the crosslinked x(10:0:1) membrane for N 2 and CH 4 was higher than that of our previously developed x(PEG/PPG:PDMS)(1:0.10) membrane, which was made of only PEG/PPG and PDMS [ 23 ]. Therefore, as was the goal of this study, it is confirmed that diffusivity can be increased by introducing the bulky and rigid adamantane unit, while also controlling the degree of crosslinking.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations